The role of international accounting standards in disclosing derivative financial instruments in the financial statements - Howrah Ahsan Khalil (Iraqi Journal for Administrative Sciences, 2024)
The purpose of this study is to know the nature of the financial instruments of both types (stocks and bonds) and modern (derivatives) and the role of international accounting standards in the disclosure in the financial statements, as well as to identify their current problems and how to invest in them and recognition and disclosure in the financial statements based on international standards For accounting that dealt with this aspect. The study used the method of analytical descriptive method by reviewing all related to financial instruments and related to this study of accounting standards, and also using the "content analysis" approach in the research to find out the amount of disclosure of derivative financial instruments in the financial statements of private banks registered in the Iraqi market for securities. And the extent to which the auditor has benefited from this disclosure in his work. This study has reached several conclusions, the most important of which are: The financial and banking institutions have tended to deal with financial instruments and include them in the financial statements. The evidence showed that the Iraqi banks that witnessed their financial reports in application of the new models of international accounting standards, whether Standard No. (32) The disclosure or IAS 39 (Financial Instruments: Recognition and Measurement) showed an improvement in the measurement and disclosure of all financial instruments and their types. The study included a number of recommendations. The most important of these were the need to amend legislation and legal texts and to regulate the regulation of the trading of derivative financial instruments in the Iraqi market for securities and enhance its basic capacity and improve its efficiency by developing and qualifying its staff, updating information systems, facilitating work procedures, To expand the channels of distribution through the organization of specialized markets to deal with and openness to the Arab and global markets, which could cause the transfer of accounting and investment culture, especially after the revolution of global communications and trade over the Internet. And encourage the establishment of companies for financial investments in terms of investment in derivative financial instruments and the formulation of a specific policy to allow the circulation of financial derivatives and the establishment of controls appropriate to its work, and to find a mechanism for the exchange of experience and mechanisms and policies in this matter.